Proposição de modalidade de prática clínica psicológica em saúde pública - Prado, Rafael Auler de Almeida (2009)
A fundamental question in psychology concerns the construction of clinical practice. Among many references, which is the best? which is the most true? Such questions, in one way or another, affect all students and perhaps many professionals. This situation was experienced, with all the intensity, with the gradual integration of psychologists in public health. The requirement of a new context of practice caused confusion and disorientation in the first professionals who have come to work in the area. It is understood that, in large part, this situation is associated with a training procedure based on technical theoretical - and therefore practices - of traditional psychology. Therefore, our objective was to propose new way to practice clinical psychology in public health. Through bibliographical and theoretical reflection, we built two articles detailing our proposal. In the first, preparatory to the second, we characterize the construction of technical-rationalist thought and its consequences for the way people think and realize that includes the development of effective clinical practices. This reflection was based on the Heideggerian perspective. In the second article, from Bachelard´s poetical conception and Pompéia e Sapienza´s psychotherapy proposal which privileges poetic language , we think about attitude, listening, language and construction to restore the poetic existential dimension of man. The conclusions of the first article pointed to the hegemony of the technical thought, however, alongside a critique of this thinking, we propose possible ways to overcome them. These possibilities concern of a way of thinking - thinking meditation - which is not only devalued and risked disappear through the construction of the contemporary. The results of the second pointed to the establishment of clinical practice we have proposed from the poetic, rather than proposing new psychotherapeutic technique. From this perspective, to account for the differences of each client - which also includes its sociocultural aspect as countless others who are - the therapist must, in the therapeutic encounter, be opened, without prior determination of its performance that predates customers behaviors. A position, a listener and, above all, a poetic encouragement, we believe, would help this process